2023
DOI: 10.3390/antiox12081538
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antioxidant, Neuroprotective, and Anti-Inflammatory Potential of Olive Leaf Extracts from Spain, Portugal, Greece, and Italy

Jose M. Romero-Márquez,
María D. Navarro-Hortal,
Tamara Y. Forbes-Hernández
et al.

Abstract: The leaves of the olive tree (Olea europaea L.) are one of the major solid wastes from the olive industry. Globally, the European Union is the largest producer of olive by-products, with Spain, Italy, Greece, and Portugal accounting for almost the entire production. Many questions remain to be solved concerning olive leaves (OL), including those related to possible differences in composition and/or biological activities depending on their geographical origin. In the present work, OL from Spain, Italy, Greece, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Lou et al [30] suggested that high TPC might contribute to the high antioxidant activity, which is probably due to the high hydrogen-donating ability of phenolic compounds [31]. The antioxidant activity of a leaf sample is also strongly related to its flavonoid content where the higher the content, the higher the radical scavenging activity [1,32,33]. Future studies can explore this further by testing multiple concentrations of the sun-dried leaf extract to optimise its antioxidant content and DPPH radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lou et al [30] suggested that high TPC might contribute to the high antioxidant activity, which is probably due to the high hydrogen-donating ability of phenolic compounds [31]. The antioxidant activity of a leaf sample is also strongly related to its flavonoid content where the higher the content, the higher the radical scavenging activity [1,32,33]. Future studies can explore this further by testing multiple concentrations of the sun-dried leaf extract to optimise its antioxidant content and DPPH radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
“…The Folin–Ciocalteu method was performed to determine TPC, and TFC quantification was performed as previously described . The absorbance was measured at 760 and 510 nm, respectively, using a Synergy Neo2 microplate reader (Biotek, Winooski, Vermont, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Making comparisons between our data and those presented in the scientific literature posed a challenge due to our lack of knowledge about the extraction method used, including any purification steps used by the company from which the extract was purchased. In addition, the yield and composition of phenols originating from different sources were found to vary depending on the genetic background of the plant and extraction techniques [22]. Cifà et al determined for OL extracts obtained with techniques such as microwave-assisted extraction, steam explosion, and pressurized liquid extraction, a value of TPC ranging from 0.0025 mg GAE /g dm to 144.2 mg GAE /g dm [23].…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 99%